Analysis of the main inconsistencies in the field environmental protection and rational use of natural resources - Dokurno, Galina S.; Khotko, Elena V. (Journal of the Belarusian State University. Ecology, 2021)
Environmental auditing is one of the ways to reduce the negative impact on our environment. The publication describes the procedure for conducting an environmental audit. The authors pay special attention to the analysis of the main resources, analyzed over the long-term practice of environmental audits, by the employees of the department of environmental certification and audit of RUE “Bel NIC” Ecology “.